The reinstatement of amphetamine-induced place preference is long-lasting and related to decreased expression of AMPA receptors in the nucleus accumbens - Cruz, F. C. [UNESP]; Marin, Marcelo Tadeu [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
A great deal of effort has been devoted to elucidating the psychopharmacology underlying addiction and relapse. Long-term neuroadaptations in glutamate transmission seem to be of great relevance for relapse to stimulant abuse. In this study, we investigated amphetamine-induced conditioned place preference during adolescence and the reinstatement of the conditioned behavior following a priming injection of the drug 1 day (adolescence), 30 days (early adulthood) and 60 days (adulthood) after the extinction test. The nucleus accumbens was dissected immediately after the reinstatement test to examine alterations in GluR1 and NR1 subunits of glutamatergic receptors. Our results showed that a priming injection of amphetamine was able to reinstate the CPP 1 and 30 days after extinction. However, it failed to reinstate the conditioned response after 60 days. GluR1 levels were decreased on days 1 and 30 but not on day 60 while NR1 levels were unaltered in the reinstatement test. Using a relapse model we found that reinstatement of amphetamine-induced conditioning place preference during adolescence is long lasting and persists through early adulthood. Decreased levels of GluR1 in the nucleus accumbens might be related to the reinstatement of amphetamine-induced conditioning place preference. (C) 2008 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: amphetamine; glutamate receptors; conditioned place preference; reinstatement; psychostimulant; adolescent